2021
DOI: 10.3390/dj9080089
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Children during Dental Care with Rubber Dam Isolation: A Randomized Controlled Study

Abstract: Background: The establishment of the dental dam improves dentist working conditions and patient protection. The purpose of this study was to analyze the behavior of the child during dental care with or without a dam. Methods: In this interventional randomized study, 51 patients are divided into two groups, one with a rubber dam and the other with cotton roll isolation. Their behavior was observed during the treatment of temporary molars. The duration of the treatment, the patient’s feeling with a visual analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Based on different studies, installing a rubber dam takes an average of 1 to 2 minutes. 15,16 This duration is insignificant in the context of the entire treatment period, therefore using the rubber dam does not materially extend the period of therapy. It should be mentioned that the duration may be affected by elements such as the number of people present in the working environment (hospital, private clinic), the workload of the dentists, their level of manual dexterity and comfort applying rubber dams, and the fear, terror, and excitement experienced by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on different studies, installing a rubber dam takes an average of 1 to 2 minutes. 15,16 This duration is insignificant in the context of the entire treatment period, therefore using the rubber dam does not materially extend the period of therapy. It should be mentioned that the duration may be affected by elements such as the number of people present in the working environment (hospital, private clinic), the workload of the dentists, their level of manual dexterity and comfort applying rubber dams, and the fear, terror, and excitement experienced by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the rubber dam is reported to cause less stress to patients than cotton rolls [ 33 ] and reduces stress for physicians during treatment as well [ 34 ]. According to the 2020 AAPD guidelines [ 35 ], rubber dam isolation is the gold standard for pulpal treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The higher success rate in our study may be explained by the combination of conscious sedation and the use of insulating rubber, a stress-reducing agent used in children during dental treatment that promotes nasal breathing and thus better inhalation of the total dose of N 2 O administered. In a recent randomized, controlled trial conducted on a sample of 51 children (mean age 6.55 ± 1.81 years), 21 of whom were treated with conscious sedation (9 with rubber dam and 12 with cotton roll isolation), Vanhée et al (2021) found that both Venham score and heart rate were lower in children treated with rubber dam and conscious sedation than in children treated with conscious sedation and cotton isolation only (p < 0.05) [47]. Similar results were also shown in a recent study that evaluated data from 112 medical records of children (mean age: 6.1 ± 1.8 years) who received restorative treatment under moderate sedation.…”
Section: Discussionmentioning
confidence: 99%